Comparative effectiveness of antiarrhythmics for out-of-hospital cardiac arrest: A systematic review and network meta-analysis. (December 2017) - McLeod, Shelley L.; Brignardello-Petersen, Romina; Worster, Andrew; You, John; Iansavichene, Alla; Guyatt, Gordon; Cheskes, Sheldon
Abstract: Background: Despite their wide use in the prehospital setting, randomized control trials (RCTs) have failed to demonstrate that any antiarrhythmic agent improves survival to hospital discharge following out-of-hospital cardiac arrest. Objective: To assess the use of antiarrhythmic drugs for patients experiencing out-of-hospital cardiac arrest (OHCA). Methods: Electronic searches of Medline, EMBASE and Cochrane Central Register of Controlled Trials were conducted and reference lists were hand-searched. Randomized controlled trials (RCTs) investigating the use of antiarrhythmic agents administered during resuscitation for adult (≥18 years) patients suffering non-traumatic OHCA were included. Direct and indirect evidence were combined in a network meta-analysis (NMA) using a frequentist approach with fixed-effects models and reported as relative risks (RR) with 95% confidence intervals (CIs). For each pairwise comparison, the certainty of direct, indirect, and network evidence was assessed using the GRADE approach. Results: 8 RCTs involving 4464 patients were combined to compare the effectiveness of 5 antiarrhythmic agents and placebo administered during resuscitation following OHCA. Lidocaine was associated with a statistically significant increase in ROSC compared to placebo (1.15; 95% CI: 1.03–1.28) and was also superior to bretylium (1.61; 95% CI: 1.00–2.60) for ROSC. When compared to placebo, both amiodarone (1.18; 95% CI: 1.08–1.30) and lidocaine (1.18; 95% CI: 1.07–1.30) were associated with a statistically significant increase in survival to hospital admission. However, no antiarrhythmic was statistically more effective than placebo for survival to hospital discharge or neurologically intact survival, and no antiarrhythmic was convincingly superior to any other for any outcome. Conclusions: Amiodarone and lidocaine were the only agents associated with improved survival to hospital admission in the NMA. For the outcomes most important to patients, survival to hospital discharge and neurologically intact survival, no antiarrhythmic was convincingly superior to any other or to placebo.